Contextual Mentoring: Theory and Practice Alignment - Mili Saha (Canadian Society for Studies in Education, 2019)
This research aims at investigating the extent to which mentoring practices are aligned with mentoring theories. Contexts of the study include formal and informal mentoring settings in five different countries around the world. A questionnaire containing eight multiple-choice and open-ended items, along with demographic items, was utilized to survey 20 experienced teachers who are either mentee or mentor in any one of those countries. Data were analyzed to examine the differences between the theoretical alignment of formal and informal mentoring practices. Results showed that formal mentoring was predominantly associated with career support, while informal mentoring was associated with psychological support for fellow workers.